Zinc and Skin Disorders - Ogawa, Youichi; Kinoshita, Manao; Shimada, Shinji; Kawamura, Tatsuyoshi (Nutrients, 2018)
The skin is the third most zinc (Zn)-abundant tissue in the body. The skin consists of the epidermis, dermis, and subcutaneous tissue, and each fraction is composed of various types of cells. Firstly, we review the physiological functions of Zn and Zn transporters in these cells. Several human disorders accompanied with skin manifestations are caused by mutations or dysregulation in Zn transporters; acrodermatitis enteropathica (Zrt-, Irt-like protein (ZIP)4 in the intestinal epithelium and possibly epidermal basal keratinocytes), the spondylocheiro dysplastic form of Ehlers-Danlos syndrome (ZIP13 in the dermal fibroblasts), transient neonatal Zn deficiency (Zn transporter (ZnT)2 in the secretory vesicles of mammary glands), and epidermodysplasia verruciformis (ZnT1 in the epidermal keratinocytes). Additionally, acquired Zn deficiency is deeply involved in the development of some diseases related to nutritional deficiencies (acquired acrodermatitis enteropathica, necrolytic migratory erythema, pellagra, and biotin deficiency), alopecia, and delayed wound healing. Therefore, it is important to associate the existence of mutations or dysregulation in Zn transporters and Zn deficiency with skin manifestations.